2001
DOI: 10.1002/ijc.1423
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of the A? subunit of protein phosphatase 2A in human gliomas in the absence of mutations in the A? and A? subunit genes

Abstract: Protein phosphatase 2A (PP2A) consists of 3 subunits: the catalytic subunit, C, and the regulatory subunits, A and B. The A and C subunits both exist as 2 isoforms (␣ and ␤) and the B subunit as multiple forms subdivided into 3 families, B, B and B؆. It has been reported that the genes encoding the A␣ and A␤ subunits are mutated in various human cancers, suggesting that they may function as tumor suppressors. We investigated whether A␣ and A␤ mutations occur in human gliomas. Using single strand conformational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 34 publications
1
54
2
Order By: Relevance
“…In apparent contradiction to our study, Collela et al (55) analyzed 58 human brain tumor samples and found that nearly half expressed little or no detectable A␣/␤ subunit protein. Intriguingly, all samples had near normal levels of catalytic and B family regulatory subunits.…”
Section: Discussioncontrasting
confidence: 99%
“…In apparent contradiction to our study, Collela et al (55) analyzed 58 human brain tumor samples and found that nearly half expressed little or no detectable A␣/␤ subunit protein. Intriguingly, all samples had near normal levels of catalytic and B family regulatory subunits.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to mutations, alterations in the expression levels of PP2A regulatory subunits are also found in human cancers. Reduction of PP2A Aa expression was found in 43% of primary human gliomas (Colella et al, 2001) and downregulation of B56g was observed in human primary melanoma specimens (Deichmann et al, 2001). In addition, three subunits of the type 2A group of phosphatases, PP4 (PP4C, PP4R2 and PP4R3), are highly expressed in human primary breast and lung tumors .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, loss or reduced expression of PR65 has been detected in human gliomas and breast cancer cell lines (Colella et al, 2001;Suzuki and Takahashi, 2003). Accordingly, in immortalised but not tumorigenic cells, expression of PR65/Aa mutants defective in binding to other PP2A subunits partially suppressed endogenous PP2A-Aa expression, activated the AKT pathway and promoted tumour formation in immunodeficient mice (Chen et al, 2005b).…”
Section: Protein Phosphatase 2a (Pp2a) a Phosphatase With Tumour Supmentioning
confidence: 94%